2021
DOI: 10.1016/j.ijpharm.2021.120259
|View full text |Cite
|
Sign up to set email alerts
|

Loss-in-weight feeding, powder flow and electrostatic evaluation for direct compression hydroxypropyl methylcellulose (HPMC) to support continuous manufacturing

Abstract: Minimizing variability in the feeding process is important for continuous manufacturing since materials are fed individually and can impact the final product. This study demonstrates the importance of measuring powder properties and highlights the need to characterize the feeding performance both offline with multiple refills and in the intended configuration for the continuous manufacturing equipment. The standard grade hydroxypropyl methylcellulose (HPMC) had material buildup on the loss-in-weight feeder bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 66 publications
1
9
0
Order By: Relevance
“…2j and k). Similar findings have been observed, to a higher extent, by Allenspach et al when feeding hydroxypropyl methylcellulose (HPMC) K4M powder and have been associated to an electrostatic powder build-up [23].…”
Section: Analysis Of the Split-feeding And Pre-blend Feeding Performancesupporting
confidence: 83%
See 1 more Smart Citation
“…2j and k). Similar findings have been observed, to a higher extent, by Allenspach et al when feeding hydroxypropyl methylcellulose (HPMC) K4M powder and have been associated to an electrostatic powder build-up [23].…”
Section: Analysis Of the Split-feeding And Pre-blend Feeding Performancesupporting
confidence: 83%
“…Therefore, there is a growing interest in characterizing the tribo-charging tendency of powders as a critical material attribute for feeding performance [19][20][21]. Powders adhering to the feeder surfaces undergo higher tribo-charging, resulting in stagnation in the hopper, reduction of the screw free volume, bearding effects at the screw outlet (i.e., adhesion to the screw outlet), and alteration to the powder trajectory during freefall motion [22] and hopper refilling [23]. This can block feeder refilling leading to poor accuracy and consistency of the dosed mass, which may propagate throughout the process and lead to products with varying content of active pharmaceutical ingredient(s) (APIs).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that cohesiveness increases with rotational speed, which is associated with more intermittent and irregular flow. This can be concern for the pharmaceutical industry as more cohesive powders can lead to increased variability and mass flow excursions outside the acceptable target range, as demonstrated by Allenspach et al [ 37 ]. Notable is the shear thinning behavior, which is observed for two grades of anhydrous lactose, two grades of lactose monohydrate and microcrystalline cellulose.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of choosing the correct grade of excipient in a CM operation is highlighted in a recent paper by Allenspach et al [ 107 ]. They found that different grades of HPMC showed different tribocharging properties when fed into a CM process from a loss in weight feeder.…”
Section: Materials Property Requirements For Continuous Manufacturingmentioning
confidence: 99%